Diels-alder cycloaddition in the synthesis of 1-azafagomine, analogs, and derivatives as glycosidase inhibitors - Salgueiro, D. A. L. (2012)
This comprehensive review deals with the synthesis of 1-azafagomine, analogs, and derivatives having the Diels-Alder cycloaddition as the key step. Most of the compounds referred are racemic or have been resolved by lipase transesterification. There are two asymmetric cycloadditions leading to 1-azafagomine or to an analog. In one case both enantiomers of 1-azafagomine were prepared together with a pair of derivatives. The study comprises glycosidase inhibition studies of the target compounds to a set of glycosidic enzymes, and evidenced molecular features that enhance or diminish their activity as glycosidase inhibitors.